2020
DOI: 10.1093/clinchem/hvaa198
|View full text |Cite
|
Sign up to set email alerts
|

Side-by-Side Comparison of Three Fully Automated SARS-CoV-2 Antibody Assays with a Focus on Specificity

Abstract: Background In the context of the COVID-19 pandemic, numerous new serological test systems for the detection of anti-SARS-CoV-2 antibodies rapidly have become available. However, the clinical performance of many of these is still insufficiently described. Therefore, we compared three commercial, CE-marked, SARS-CoV-2 antibody assays side by side. Methods We included a total of 1,154 specimens from pre-COVID-19 times and 65 sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
128
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 25 publications
22
128
0
Order By: Relevance
“…The higher overall pooled sensitivity reported in this systematic review and meta -analysis compared to our study is likely due to its higher combined sample size of over 29,000 tests and the fact that 60% of our samples were analyzed within three weeks of PCR positivity. Perkmann, et al also evaluated Abbott anti-SARS-CoV-2 IgG, DiaSorin anti-SARS-CoV-2 IgG, and Roche anti-SARS-CoV-2 total and reported sensitivities more similar to those observed in our study, ranging from 83.1% to 89.2% in 65 samples from COVID-19 patients evaluated ≥ 14 days after symptom onset [22] . However, as is apparent in our study and others [10] , [23] , sensitivity of the different immunoglobulin classes differ depending on days post symptom onset or PCR positivity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The higher overall pooled sensitivity reported in this systematic review and meta -analysis compared to our study is likely due to its higher combined sample size of over 29,000 tests and the fact that 60% of our samples were analyzed within three weeks of PCR positivity. Perkmann, et al also evaluated Abbott anti-SARS-CoV-2 IgG, DiaSorin anti-SARS-CoV-2 IgG, and Roche anti-SARS-CoV-2 total and reported sensitivities more similar to those observed in our study, ranging from 83.1% to 89.2% in 65 samples from COVID-19 patients evaluated ≥ 14 days after symptom onset [22] . However, as is apparent in our study and others [10] , [23] , sensitivity of the different immunoglobulin classes differ depending on days post symptom onset or PCR positivity.…”
Section: Discussionsupporting
confidence: 86%
“…A meta -analysis reported overall specificity for anti-SARS-CoV-2 IgG and IgM assays of 99.1% (44 studies included) and 98.7% (41 studies included), respectively [9] . Perkmann, et al previously reported specificities of 99.2% for Abbott anti-SARS-CoV-2 IgG, 98.3% for DiaSorin anti-SARS-CoV-2 IgG, and 99.7% for Roche anti-SARS-CoV-2 total using over 1,154 pre-COVID-19 specimens [22] . Other studies reported specificities of 99.9% using 1,020 serum specimens collected prior to SARS-CoV-2 circulation [25] and 99.3% using 107 serum specimens collected either before the emergence of SARS-CoV-2 or from PCR negative patients [26] for Abbott anti-SARS-CoV-2 IgG.…”
Section: Discussionmentioning
confidence: 96%
“…6 In this study, we used the Elecsys® Anti-SARS-CoV-2 electrochemiluminescence immunoassay, which presented a high specificity rate of 99•7% (95%CI 99•2-100•0) and a positive predictive value (PPV) of 97•4% with a 10% seroprevalence rate. 31 We have likely achieved a higher PPV because the prevalence in our survey was four times that seroprevalence rate. It has been shown that electrochemiluminescence immunoassays present higher sensitivity than lateral flow immunoassays.…”
Section: Resultsmentioning
confidence: 77%
“…In the two-test approach, the overall result was considered positive if the sample tested positive by both assays and negative if the sample was negative using one or both assays. When calculating the positive predictive value (PPV) or negative predictive value (NPV) at various prevalence rates, assay sensitivity was defined as the observed sensitivity using samples collected >14 days after symptom onset (when sensitivity is reported to be its highest) ( 8 10 ). Specificity was defined (for PPV and NPV calculations) as the value obtained when all control samples were combined.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the relatively low prevalence of COVID-19 infection in many tested populations and the implications of false-positive results for patient care and public health measures, the Centers for Disease Control and Prevention (CDC) has determined that highly specific (≥99.5%) serologic tests are required to provide adequate positive predictive value (PPV) ( 7 ). Although high specificity is reported for many commercial SARS-CoV-2 serologic assays, not all of them consistently meet this specificity threshold (see Table S1 in the supplemental material) ( 8 10 ). A potential approach to ensure consistently high specificity involves the application of a two-test algorithm in which reactivity using one assay is confirmed using a different (orthogonal) assay.…”
Section: Introductionmentioning
confidence: 99%